When expectations become aspirations: Reference-dependent preferences and liquidity constraints - Kramer, Berber (International Food Policy Research Institute, 2015)
A large body of literature suggests that consumers derive utility from gains and losses relative to a reference point. This paper shows that such reference dependence can affect savings in opposite directions depending on whether people face liquidity constraints. Existing models for wealth and intertemporal choice predict that reference dependence reduces savings but these models abstract from liquidity constraints. Introducing a liquidity constraint, I find that reference dependence can increase optimal savings for people without access to credit. Liquidity constraints force them to take part of an income loss in early periods, which may induce those who are reference dependent to concentrate the full loss in early periods and save in order to eliminate future losses. Further, anticipating a liquidity constraint raises the expected level of future consumption and thus the expectations-based reference point for future periods, creating a second savings motive. This underscores the impact that financial market imperfections can have when applying reference-dependent models in low-income settings.